Reforms of the Roman calendar – remarks on studies of Roman law - Kosior, Wojciech Jan (The Opole Studies in Administration and Law, 2020)
This article discusses the problem of reforms that affected the Roman calendar from its formal establishment up to the time of its formation to what we now know. The need to analyze that matter arose on the occasion of studies on the importance of age in Roman law and precise determination whether 1 year always meant 365 days.